How genetic determinism and genetic diseases are presented in textbooks of 14 countries - Silva, Carla (2009)
The purpose of the present study was to analyse whether "Genetic Determinism" and "Genetic anomalies" are present in the textbooks of 14 countries and, being present, how these issues are addresses, for the age group of 14 to 18 years old. These countries are involved in the international project “Biohead-citzen”(European Project FP6 STREP Biohead-Citizen; CIT2-CT2004-506015) in which one of the topics is "Human Genetics" Results show that both terms “Genetic program" and "Genetic information", carrying different meanings, are expressed in textbooks with no clear association to the countries culture. Some of the genetic anomalies referred in textbooks are consistently present in all textbooks whereas others vary a lot from country to country. The association of the socio-cultural influences with this issue is now a matter of research.